English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

verify the identity by transforming the left side into the right side

2006-11-08 09:01:16 · 3 answers · asked by scoota 1 in Science & Mathematics Mathematics

3 answers

cot(-x)cos(-x) + sin(-x) = -csc x

LHS = cot(-x)cos(-x) + sin(-x)
= cos(-x)/sin(-x) * cos(-x) + sin (-x)
= cos²(-x)/sin(-x) + sin²(-x)/sin(-x)
= (cos²(-x) + sin²(-x))/sin(-x)
= 1/sin(-x)
= 1/-sin(x)
= -csc(x)
= RHS

2006-11-08 09:06:16 · answer #1 · answered by Wal C 6 · 0 0

LHS = cot(-x)cos(-x) + sin(-x)
= cos(-x)/sin(-x) * cos(-x) + sin (-x)
= cos²(-x)/sin(-x) + sin²(-x)/sin(-x)
= (cos²(-x) + sin²(-x))/sin(-x)
= 1/sin(-x)
= 1/-sin(x)
= -csc(x)
= RHS

WOW that was hard im in 6 grade that was like imposible

2006-11-08 09:22:52 · answer #2 · answered by maggieissohot 1 · 0 0

(cos(-x)/sin(-x))*cos(-x)+sin(-x)
=>
cos^2(-x)/sin(-x)+sin(-x)
=>
(1-sin^2(-x))/sin(-x)+sin(-x)
=>
1/sin(-x)-sin(-x)+sin(-x)
=>
1/sin(-x)
=>
csc(-x)
=>
-csc(x)

Another way.... :)

2006-11-08 09:25:38 · answer #3 · answered by Alejandra B 2 · 0 0

fedest.com, questions and answers